China's capital flight: Pre- and post-crisis experiences. (September 2016) - Cheung, Yin-Wong; Steinkamp, Sven; Westermann, Frank
Highlights: We study the World Bank residual and trade misinvoicing measures of capital flight. China's capital flight and its determinants are affected by the crisis in 2007. Capital flight exhibits a weakened response to covered interest differentials. The post-2007 behavior is influenced by quantitative easing and other factors. Our empirical results highlight the challenges of managing China's capital flight. Abstract: We study China's illicit capital flow and document a change in its pattern. Specifically, we observe that China's capital flight, especially the one measured by trade misinvoicing, exhibits a weakened response in the post-2007 period to the covered interest disparity, which is a theoretical determinant of capital flight. Further analyses indicate that the post-2007 behavior is influenced by quantitative easing and other factors including exchange rate variability, capital control policy and trade frictions. Our study confirms that China's capital flight pattern and its determinants are affected by the crisis event. Further, both the canonical and additional explanatory variables have different effects on different measures of capital flight. These results highlight the challenges of managing China's capital flight, which requires information on the period and the type of capital flight that the policy authorities would like to target.